Análise estatística de dados ultrassônicos para a seleção de características da alvenaria que comprometem sua estabilidade - Rodrigues, Renan Vinicius (Universidade Federal de São Carlos, 2020)
The stability of buildings is a concern that is gaining more and more focus in the current world, since knowing whether the masonry of a particular building is compromised reduces the chances that it will cause economic losses and / or risk the health and safety of people who attend it. For the modifications to the structures to be minimal when analyzing the stability of a construction, non-destructive tests using ultrasonic waves appear as a useful tool to check the condition of a masonry and, if applied to constructions with different characteristics, allow to study how these characteristics modify the speed of propagation of the wave inside and how they interfere in the stability of the construction. In this work, therefore, we analyze and identify which aspects (bricks, grout or interface of both; presence or not of voids on the walls and the height of the measurement in relation to the ground) most impact the speed of the ultrasonic waves inside the walls and, consequently, we verify how the wave behavior reflects the stability of the construction.
Statistical analysis of ultrasonic data for the selection of masonry characteristics that compromise its stability
Keywords: Modelos mistos; Processos Gaussianos; Estabilidade das construções; Processos não destrutivos; Mixed models; Gaussian process; Building stability; Non destructive process; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO